Pragmatism: exploring public administration's policy imprint - Shields, Patricia M. (1996)
Public administrators are often described as pragmatic. Yet few scholars have investigated what this might mean. This article introduces the notion of policy imprint - the effect that professional groups have on policy. Pragmatism is championed as an organizing principle that explains the public administration (PA) policy imprint. The pragmatism of William James and John Dewey is described and applied to PA. Because PA leaves its imprint where theory and practice meet, the article examines the theory-practice nexus through the lenses of pragmatism. Finally, pragmatism's link to democracy is developed. - Reproduced
Keywords: Public administration